Flat-Top and Stacking-Fault-Free GaAs-Related Nanopillars Grown on Si Substrates - Kouta Tateno; Guoqiang Zhang; Hideki Gotoh; Tetsuomi Sogawa (Journal of Nanotechnology)
The VLS (vapor-liquid-solid) method is one of the promising techniques for growing vertical III-V compound semiconductor nanowires on Si for application to optoelectronic circuits. Heterostructures grown in the axial direction by the VLS method and in the radial direction by the general layer-by-layer growth method make it possible to fabricate complicated and functional three-dimensional structures in a bottom-up manner. We can grow some vertical heterostructure nanopillars with flat tops on Si(111) substrates, and we have obtained core-multishell Ga(In)P/GaAs/GaP nanowires with flat tops and their air-gap structures by using selective wet etching. Simulations indicate that a high-𝑄 factor of over 2000 can be achieved for this air-gap structure. From the GaAs growth experiments, we found that zincblende GaAs without any stacking faults can be grown after the GaP nanowire growth. Pillars containing a quantum dot and without stacking faults can be grown by using this method. We can also obtain flat-top pillars without removing the Au catalysts when using small Au particles.